Monitoring oomycetes in water: combinations of methodologies used to answer key monitoring questions - Pettitt, Tim R. (Frontiers in Horticulture, 2023)
Monitoring oomycete populations and communities in bodies of water is vital in developing our understanding of this important group of fungus-like protists that contains many serious pathogens of both crops and wild plants. The methodologies involved in monitoring oomycetes are often presented as a developmental hierarchy, progressing from ‘traditional’ culture-based techniques through immunological techniques and basic PCR to qPCR and metagenomics. Here, techniques are assessed according to the roles they can perform in relation to four stages of the monitoring process: capture, detection and identification, viability determination, and quantification. Possible synergies are then considered for the combined use of different techniques in addressing the various needs relating to different questions asked of monitoring, with an emphasis on the continuing value of cultural and immunodiagnostic procedures. Additionally, the exciting future presented by the ongoing development and improvement of metabarcoding and the use of high throughput sequencing techniques in the measurement and monitoring of oomycete inoculum to determine and mitigate plant disease risks is addressed.